Polycyclic aromatic hydrocarbons in the work atmosphere – determination of area-specific concentrations and job-specific exposure in a vertical pin Søderberg aluminum plant - Bjørseth, Alf; Bjørseth, Olav (Scandinavian Journal of Work, Environment & Health, 1981)
Polycyclic aromatic hydrocarbons (PAH) and particulates in the work atmospheres of the potrooms and anode paste plant of an aluminum reduction plant were determined by stationary and personal sampling and a glass capillary gas chromatographic method. The relative distribution of PAH (PAH profile), the fraction of PAH on particulates, and the ratio between particulate and gaseous PAH were also determined. The PAH profile was found to be similar to that found for another aluminum plant. The PAH fraction of particulate matter was generally between 1 and 4%, and the ratio between particulate and gaseous PAH in the potrooms varied from 0.2 to 1. The occupational exposures were determined from an analysis of a total of 167 personal samples. For most job categories, the geometric mean of the exposure values was higher than 40 µg/m3, spike pulling having the highest exposure of the categories measured.
Keywords: aluminum; aluminum plant; aluminum reduction plant; analysis; area-specific concentration; benzo(a)pyrene; coal tar; coal tar pitch volatile; exposure; gas chromatography; glass capillary gas chromatography; job-specific exposure; occupational exposure; PAH; polycyclic aromatic hydrocarbon; sampling; work atmosphere